Impact of solvent properties on the precipitation of active pharmaceutical ingredients - Schikarski, Tobias; Trzenschiok, Holger; Avila, Marc; Peukert, Wolfgang (Powder Technology, 2023)
In antisolvent precipitation, water and an organic drug-containing solvent induces particle formation. For each water-solvent mixture, the fluid properties such as viscosity, density and diffusion coefficient but also the drug solubility depend nonlinearily on the fluid mixture compositions. Each property in itself has a strong impact on the solid formation, and thus on the outcome of the precipitation. The simulation framework recently developed by Schikarski et al. [1] allows investigating separately the impact of each fluid property on the precipitation. For a T-mixer and a novel 3-inlet-mixer, we first show that the viscosity and density variations largely determine the macroscopic mixing behavior and, thus, the build-up of supersaturation. The composition-dependent diffusion properties of the drug molecules largely govern the transport-controlled nucleation and particle growth at small scales. In a second step, we numerically predict the experimentally obtained full particle size distribution of the precipitated Ibuprofen nanoparticles using different water-solvent mixtures and different operating conditions. Our numerical results are in excellent agreement with our experimental measurements using ethanol, methanol and 2-propanol as solvents.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Active pharmaceutical ingredients; Antisolvent precipitation; Binary mixtures; Computational fluid dynamics; Nucleation and growth of particles; Population balance equation; Water; ethanol; methanol; 2-propanol